Implementasi Project Based Learning (PjBL) Berorientasi Pengembangan Karakter Siswa yang Kritis - Suprapto, Suprapto; Sulaeman, Maryam (Jurnal Inovasi Pendidikan MH Thamrin, 2022)
The Distance Learning Process is a solution to the Covid-19 pandemic situation which is considered more effective and efficient, but there are various kinds of problems, not only educators and students, but also parents. The problems faced are the difficulty of supervising students who lack honesty and discipline in doing and collecting assignments, supervising students who do not focus on learning, difficult to adapt which make character development less effective. The specific purpose of the research is to produce a Project Based Learning model that can improve students' ability to solve problems, and it is hoped that students will be more active, independent and responsible. The method used is Action Research to produce certain products, and test the effectiveness of the product through various stages and validation with the following steps: 1) planning, 2) acting, 3) monitoring, and 4) reflecting. The results of the study found that scores were still very lacking in the first and second cycles in fostering a critical attitude to students, but in the third cycle significant improvements were found. This is evidenced in the reflection of most students. Future research requires a model for applying critical thinking in higher education